A Comparison of the Clinical Outcomes of Haploidentical Transplantation and Other Graft Sources in Acute Lymphoblastic Leukemia: A Systematic Review and Meta-Analysis - Owattanapanich W. (2023)
Background: Most likely due to the availability of potential stem cell sources, there appears to be a growing usage of haploidentical (haplo) donors for cases of acute lymphoblastic leukemia involving high-risk features or relapse. Patients and Methods: This study compared the outcomes of stem cell transplantations (SCTs) using haplo and other stem cell sources, namely, matched sibling donors (MSDs), matched unrelated donors (MUDs), and cord blood transplantations (CBTs). Literature searches were conducted of the MEDLINE and Embase databases from inception to December 2020. Results: Twenty-eight studies were examined (17 retrospective and 11 prospective). There were no significant differences in the overall survival of haplo and those of the other stem-cell sources. For haplo versus matched donor (MSD or MUD), the pooled odds ratio (OR) was 0.94 (95% CI, 0.79-1.12; I2, 22%); while for haplo versus CBT, the OR was 1.24 (95% CI, 0.78-1.96; I2, 28%). The cumulative relapse incidence was significantly higher for MSD than haplo (OR, 0.69; 95% CI, 0.48-0.99; I2, 48%). Both grade II-IV acute and long-term graft-versus-host disease (GVHD) were significantly higher for haplo than MSD (OR, 1.78; 95% CI, 1.15-2.74; I2, 28%; and OR, 1.33; 95% CI, 1.00-1.77; I2, 14%, respectively). The other clinical outcomes did not demonstrate any statistical differences. Conclusion: The outcomes of patients treated with haplo-SCT appear comparable with those of the SCTs using other sources. The higher probability of developing GVHD supports the need for a novel method to harness T-cell alloreactivity